Effects of attention without perceptual awareness on motor responses, memory and behavior - Lin, Jeffrey Yu-Ting (My University, 2012)
Our everyday visual experience is strongly affected by attention. Visual attention can enhance or prioritize the processing of specific stimuli over the overwhelming number of other sensory inputs by selecting spatial locations, features, objects, and even time. For example, attending to a particular feature such as the color of an object produces a global facilitation of processing for stimuli that share that feature; alternatively, cueing attention to a particular location can enhance sensitivity to visual input at the cued location. A critical question for understanding the relationship between attention and consciousness is whether awareness is required for this type of prioritized attentional selection. It has been suggested that visual attention can only be affected by consciously perceived events; however, we identified three novel and surprising results about the nature of attention and how it can influence our motor responses, memory and behavior without perceptual awareness. (1) We demonstrated how the visual system can extract behaviorally relevant details from a visual scene and automatically categorize threatening versus non-threatening images at a level of precision beyond our conscious perceptual capabilities in the absence of perceptual awareness. (2) We found that memory for scenes was enhanced when presented concurrently with a behaviorally important target--this is evidence of a mechanism where traces of a visual scene are automatically encoded into memory at behaviorally relevant points in time regardless of the spatial focus of attention. (3) We found evidence for a previously unknown exogenous cueing mechanism for feature-based attention where visual attention responds reflexively and rapidly in response to color cues.
Thesis (Ph.D.)--University of Washington, 2012
Keywords: cognition; exogenous cues; visual attention; visual memory; Psychology; Psychology